2022
DOI: 10.1039/d2nr01780f
|View full text |Cite
|
Sign up to set email alerts
|

Protein encapsulation within the internal cavity of a bacterioferritin

Abstract: The controlled, reversible dissociation of bacterioferritin allows the trapping of guest molecules such as proteins within the internal cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…Motivation for this work was driven by two factors: an ever-expanding need to produce novel materials with diverse functionalities from self-assembling biomolecules, and the need to further understand how to incorporate additional sophistication into biological architectures. The goal was to design several structural features into the Bfr scaffold to provide additional versatility to the ferritin class of protein cages, a focus of great current interest [ 7 , 58 , 59 , 60 ]. The implementation of engineered non-native affinity linkers in the interior of Bfr and the presence of chemically modifiable heme cofactors has demonstrated that the interior surface can be controllably modified to encapsulate a diverse set of molecular guests all the while employing the same scaffold .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivation for this work was driven by two factors: an ever-expanding need to produce novel materials with diverse functionalities from self-assembling biomolecules, and the need to further understand how to incorporate additional sophistication into biological architectures. The goal was to design several structural features into the Bfr scaffold to provide additional versatility to the ferritin class of protein cages, a focus of great current interest [ 7 , 58 , 59 , 60 ]. The implementation of engineered non-native affinity linkers in the interior of Bfr and the presence of chemically modifiable heme cofactors has demonstrated that the interior surface can be controllably modified to encapsulate a diverse set of molecular guests all the while employing the same scaffold .…”
Section: Resultsmentioning
confidence: 99%
“…Substantial efforts are being made to utilize multimeric, self-assembling protein complexes in bionanotechnological applications [ 1 , 2 , 3 , 4 , 5 ]. Nanodimensional cage-proteins such as ferritins [ 6 , 7 ], cavity-containing enzymes [ 8 ], chaperonins [ 9 ], virus capsids [ 10 , 11 , 12 ], vault proteins [ 13 , 14 ], microbial microcompartments [ 15 , 16 , 17 ], and encapsulins [ 18 ] can be engineered with some precision to accommodate guest molecules within their hollow interior cavities. The strategic design of protein cages has resulted in the creation of biomolecular platforms capable of encapsulating a diverse set of guest molecules ranging from drugs [ 8 , 19 ], metal nanoparticles [ 20 , 21 ], enzymes [ 22 , 23 ], polymers [ 24 , 25 ], and oligonucleotides [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 60 ] employed TmFtn to encapsulate positively supercharged green fluorescent protein (+36GFP) that four +36GFP molecules were loaded into one TmFtn nanocage. Bacterioferritin (Bfr), which contained a heme prosthetic group at the interface of each subunit dimer, showing similar salt-induced disassembly/reassembly behavior [ 75 , 61 ]. Bradley et al.…”
Section: Loading Methods For Ferritin-based Nanomedicinementioning
confidence: 99%
“…Bradley et al. [ 61 ] also utilized this loading strategy to encapsulated ferredoxin into Bfr nanocage. Although salt-induced drug loading method was gentler, it has not been widely used since these archaeobacterial ferritins may cause stronger immune reaction compared with human ferritin.…”
Section: Loading Methods For Ferritin-based Nanomedicinementioning
confidence: 99%